(untitled) ("Journal "U". Economy. Management. Finance.", 2018)
Staff is a fundamental part of any organization and one of the most important resources for innovative development. The selection of new methods of personal development management is an important requirement for the effective functioning of all organizations. It is impossible to answer the question without using of innovative methods of personnel management, which is an urgent topic for the management of companies in our time.